The Decolonial Turn: Towards a Southern Theory in Media Studies - Moyo, Last (The Decolonial Turn in Media Studies in Africa and the Global South, 2020)
This chapter argues that media and communication studies lie at the centre of Euro-American modernity. There is no doubt that the interdiscipline is the bastion of the coloniality of knowledge and its decolonization is way overdue given the indispensability of communication in the political, cultural, and epistemic liberation in the Global South. As a field as well as a social process, ‘mass communication was instrumental in the twentieth century crusade of modernity where it remained a key element in the unfolding of the future’ (Hardt in Myths for the Masses: An Essay on Mass Communication. Blackwell, London, p. 3, 2004). Decoloniality arises as a necessary moral and epistemic project to develop a nuanced praxis of decolonization agenda in the interdiscipline. Decolonization must decentre Eurocentrism and imperial theories and deprovincialize the marginalized alternate epistemologies in media and communication studies. The aim of decolonial turn is not to reproduce a new Hegelian hierarchies or new knowledge power structures in the field, but to give birth to a truly multicultural critical media theory that emerges from intercultural and trans-epistemic dialogue between the geographic Northern and Southern epistemologies.